Fairness in Re-Election: Examining Resignation Rules for Public Officials Through the Lens of Equality Before the Law - Nurma Chrismawantika (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The principle of equality before the law, which is the foundation of the country's legal system as stated in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, emphasizes that all citizens have an identical position in the realm of law and government without any exceptions. However, the regulation of the Resignation of Public Officials who intend to run for re-election to public office shows variations among the various existing constitutional regulations. This disparity of rules has the potential to create unequal treatment of Public Officials, which substantively violates the principle of equality before the law mandated by the 1945 Constitution of the Republic of Indonesia. This study aims to identify and analyze the suitability of Resignation arrangements for Public Officials who will run for re-election to public office according to the perspective of equality before the law in the Constitution. This research is a normative juridical study with a statutory analysis approach, conceptual approach, and case study approach to explore legal concepts and provide comprehensive juridical prescriptions. Based on the research findings, the implementation of the law related to the Resignation of Public Officials who are running for office is still not fully in line with the principle of equality before the law, so that regulatory reconstruction is needed to create equality before the law for all potential Public Officials.